Implementasi Pembelajaran TIK: Pendampingan Penggunaan Microsoft Word sebagai Media Penunjang Belajar Siswa SD NEGERI 2 Mersi - Tsuroya Salmah; Meli Lestari; Yumna Azizah; Nadea Nawal Syefira; Ito Setiawan (JURNAL ILMIAH NUSANTARA, 2026)
In the current digital era, computer proficiency has become an essential basic skill for children, even at the elementary school level. However, many students still lack the opportunity to explore word processing software in depth. This program was initiated to provide hands-on mentoring in the use of Microsoft Word for students at SD NEGERI 2 MERSI. Using a "learning by doing" approach, students were introduced to basic menus, practiced typing school assignments, and learned how to format documents neatly. The results show that this mentoring successfully improved the students' technical skills and confidence in using computers as study tools. Beyond just mastering the application, students are now better prepared to utilize technology to complete their academic tasks more creatively. This program demonstrates that early exposure to technology is highly effective in preparing the younger generation to face the challenges of the digital world.